Digital Communication Strategy in Organizational Operations: Adaptation and Transformation in the Digital Era - Bahrudin Hasan (Journal of Dialogos, 2026)
This study examines digital communication strategies adopted by organizations in adapting to and transforming within the digital era. The rapid development of digital technology has fundamentally altered organizational communication patterns, requiring adaptive strategies that encompass the use of digital platforms, media management, and internal and external communication systems. Employing a systematic literature review (SLR) methodology combined with qualitative case analysis across five Indonesian organizations, this research identifies four key dimensions of digital communication strategy: platform architecture and integration, content strategy and management, audience engagement and relationship building, and organizational culture and digital literacy. The findings reveal three distinct organizational adaptation patterns, reactive, planned, and proactive, and identify six critical success factors for effective digital communication strategy implementation. Organizations that adopt integrated, strategic approaches demonstrate superior stakeholder engagement, operational efficiency, and organizational resilience. This research contributes to the theoretical framework of organizational communication in the digital age and offers practical implications for communication practitioners and organizational leaders navigating digital transformation.